Intentional acceptance of social robots: Development and validation of a self-report measure for children. Issue 139 (July 2020) - de Jong, Chiara; Kühne, Rinaldo; Peter, Jochen; van Straten, Caroline L.; Barco, Alex
Highlights: Reliable and valid scale for children's intentional social robot acceptance. All four indicators loaded positively and significantly on the latent construct. Partial metric and scalar invariance was established for boys and girls. Abstract: As the field of child-robot interaction (CRI) is still young, little consensus exists on the conceptual and methodological approach to the study of children's intentional acceptance of social robots, an important antecedent and an outcome of CRI. Against this background, the goal of this study was to develop and validate a self-report measure of intentional social robot acceptance (i.e., intention to use) for children. Partly based on measures for adults, we developed a four-item scale for children's intentional acceptance of social robots. We administered the measure along with the validation measures (i.e., enjoyment, social presence, and social anxiety) among 87 Dutch children aged 7 to 11 years. Our measure reliably and validly assessed children's intentional acceptance of social robots. As children are increasingly likely to encounter social robots in their lives, our measure may help to improve the study of children's acceptance of social robots and its pertinent processes.